Relação entre o consumo alimentar habitual de vitamina D, estado nutricional e estilo de vida em todas as faixas etárias de uma mesma população - Sebadelhe, Vittória Regina Rodrigues Jacob (2015)
In addition to the importance of vitamin D for bone health, is of great interest to elucidate its relationship with obesity. The objective of this study was to examine the relationship between habitual dietary intake of vitamin D and body weight in all age groups of the same population. A cross-sectional population-based study, involving 866 individuals from a city in northeastern Brazil. Demographic data were collected and 24-hour recalls, and held anthropometric assessment. The adequacy of nutrients was estimated by adjusting the person variance of nutrient intake. Applied to multiple regression between variables. In the total sample, 45.27% of the participants were overweight or obese. The average habitual intake of vitamin D is approximately 2mg. There was a relationship between habitual dietary intake of vitamin D and body weight in the total sample (t = -2.34, p = 0.019), in adolescents (t = -2.51, p = 0.012) and adults (t = -2.75, p = 0.006). For children and the elderly these relationships were observed. The existence of a relationship between habitual dietary intake of vitamin D and body weight in adolescents and adults but not in children and the elderly, suggests that those most vulnerable age groups the metabolic pathways of vitamin D, which may favor weight loss, are not being stimulated or active, although the intake of children was higher and the elderly similar to the other groups.